2010
DOI: 10.1074/jbc.m110.172072
|View full text |Cite
|
Sign up to set email alerts
|

Two Independent Histidines, One in Human Prolactin and One in Its Receptor, Are Critical for pH-dependent Receptor Recognition and Activation

Abstract: Human prolactin (hPRL), a member of the family of hematopoietic cytokines, functions as both an endocrine hormone and autocrine/paracrine growth factor. We have previously demonstrated that recognition of the hPRL⅐receptor depends strongly on solution acidity over the physiologic range from pH 6 to pH 8. The hPRL⅐receptor binding interface contains four histidines whose protonation is hypothesized to regulate pH-dependent receptor recognition. Here, we systematically dissect its molecular origin by characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
49
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(54 citation statements)
references
References 46 publications
5
49
0
Order By: Relevance
“…The recycling mannose lectin ERGIC-53 binds cargo in the ER and releases it in the slightly more acidic ER-Golgi intermediate compartment (ERGIC), and cargo release requires protonation of conserved His 178 (12). A recent His-to-Ala mutagenesis study of the ligand-receptor binding interface showed that the evolutionarily conserved residues His 180 in human prolactin and His 188 in the prolactin receptor are critical for pH-dependent ligand binding at the cell surface and release in acidic endosomes (13). We have used phylogenetic comparisons to identify candidate pH-sensing His residues in VWF and homologous gel-forming mucins, which were functionally evaluated by mutagenesis.…”
mentioning
confidence: 99%
“…The recycling mannose lectin ERGIC-53 binds cargo in the ER and releases it in the slightly more acidic ER-Golgi intermediate compartment (ERGIC), and cargo release requires protonation of conserved His 178 (12). A recent His-to-Ala mutagenesis study of the ligand-receptor binding interface showed that the evolutionarily conserved residues His 180 in human prolactin and His 188 in the prolactin receptor are critical for pH-dependent ligand binding at the cell surface and release in acidic endosomes (13). We have used phylogenetic comparisons to identify candidate pH-sensing His residues in VWF and homologous gel-forming mucins, which were functionally evaluated by mutagenesis.…”
mentioning
confidence: 99%
“…In tumor contexts, the high glycolytic activity and proton extrusion by cancer cells is known to acidify the extracellular milieu (42). Knowing that PRL binding to the PRLR is strongly pH-dependent (43)(44)(45), the reduction of complex lifetime due to tumor acidification should reduce signaling to such an extent that it ultimately brings STAT5 activation into the regulatory range (Fig. 10).…”
Section: Discussionmentioning
confidence: 99%
“…1D). 11,14,18 His188 is found at the interface of the high-affinity binding site 1, 12,13,18 where it forms a polar contact (i.e., a noncovalent bond) with prolactin ( Fig. 1E) and contributes to a four-member histidine ring, formed by His188 in the prolactin receptor and three histidines of prolactin (His27, His30, and His180), which stabilizes ligand binding and determines the pH dependence of receptor activation.…”
Section: Prediction Of Effects Of the Prlr Mutationmentioning
confidence: 99%
“…13,18,19 Prolactin interacts with each extracellular domain of the dimeric prolactin receptor, first by means of a high-affinity (nanomolar range) binding site 1, and second, by means of a lowaffinity (micromolar range) binding site 2 ( Fig. 1D).…”
Section: Prediction Of Effects Of the Prlr Mutationmentioning
confidence: 99%
See 1 more Smart Citation